IMPLEMENTASI PRIORITAS PENGGUNAAN DANA DESA TERHADAP MASYARAKAT KAMPUNG SALOR INDAH KABUPATEN MERAUKE - Syahruddin Syahruddin (Universitas Musamus,Merauke,Papua, 2019)
The priority implementation of the Dana Desa is a government program to improve the standard of living of the people of Kampung Salor Indah in improving the quality of life, welfare, poverty alleviation and public services. The research objective is to describe and analyze the priority of the use of the Dana Desa towards the Salor Indah village community in Merauke Regency. Data analysis technique is qualitative which uses an interactive analysis model. The results of the study illustrate that prioritizing the use of Dana Desa is very helpful in village development. This is implemented through various community empowerment activities, improvement of infrastructure facilities for health service centers, education and infrastructure.